2017
DOI: 10.1080/09712119.2017.1394859
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of rumen fermentation and microbial community differences between water buffalo and Jersey cows under similar feeding conditions

Abstract: Differences in rumen volatile fatty acids (VFAs), microbial population and community composition between water buffalo and Jersey cows were compared to explore the effects of animal species on ruminal microbiota. Ruminally fistulated buffalo (n = 4) and Jersey cows (n = 4) with similar body weights were selected and provided with similar diets. After feeding for 30 days, rumen fluid was collected to quantify the ruminal VFA, and determine microbial population and community composition. Results revealed that co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
29
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 37 publications
(41 reference statements)
20
29
1
Order By: Relevance
“…At the genus level, Prevotella was the most dominant genera , followed by Butyrivibrio and Ruminococcus, which all belong to the phylum Firmicutes (Figure ). The result is consistent with previous studies in which Prevotella was the most dominant genus in all buffaloes (Iqbal et al, ; Lin et al, ). In dairy cows, Lima et al () also found that the genus Prevotella was the most dominant genus.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…At the genus level, Prevotella was the most dominant genera , followed by Butyrivibrio and Ruminococcus, which all belong to the phylum Firmicutes (Figure ). The result is consistent with previous studies in which Prevotella was the most dominant genus in all buffaloes (Iqbal et al, ; Lin et al, ). In dairy cows, Lima et al () also found that the genus Prevotella was the most dominant genus.…”
Section: Resultssupporting
confidence: 93%
“…In dairy cows, Lima et al (2015) also found that the genus Prevotella was the most dominant genus. However, the second and third most abundant genus was Butyrivibrio and Ruminococcus, which was inconsistent with previous study (Iqbal et al, 2018;Lima et al, 2015;Lin et al, 2015), the diet and individual differences may be account that.…”
Section: Microbiota Composition Of Lactating Buffalocontrasting
confidence: 92%
“…The current study found that TVFA as well as the proportion of VFA levels in Swamp were higher than those in Murrah cross when tested with Diet A and Diet C, while not much different found when tested with Diet B; indication that the pattern of rumen fermentation was different between both breeds. These results are consistent with ndings of Iqbal et al [40] and Chanthakhoun et al [41], which also indicated different in levels of TVFA, short chain fatty acids percentage and C2:C3 ratio in in vitro fermentation study in Swamp and Murrah cross buffaloes that were fed with different proportion diet of forage and supplement.…”
Section: Effect Of Different Diets On In Vitro Rumen Fermentation Parsupporting
confidence: 92%
“…However, in spite of representing two major methane emitting species, the comparative diversity analysis of methanogens between cattle and buffaloes has not been extensively investigated. There is only one report where methanogen abundances between cattle and buffaloes were compared [38]. Community structure analysis from their study revealed a signi cantly higher abundance of Methanobrevibacter genus in Jersey cows than in water buffaloes.…”
Section: Discussionmentioning
confidence: 99%
“…In India, cattle are poorly fed and comparatively ine cient milk producer than the buffaloes [44] which leads to the higher distribution of Mbr. gottschalkii through higher H 2 concentration and acetate/propionate (A/P) ratio [38,45]. The difference in the distribution of Mbr.…”
Section: Discussionmentioning
confidence: 99%